2023
DOI: 10.1002/cmdc.202200631
|View full text |Cite
|
Sign up to set email alerts
|

A Reinvestigation of the Role of the Sorbic Acid Tail on the Antibacterial and Anti‐Tuberculosis Properties of Moiramide B

Abstract: Due to worldwide increasing resistances, there is a considerable need for antibacterial compounds with modes of action not yet realized in commercial antibiotics. One such promising structure is the acetyl-CoA carboxylase (ACC) inhibitor moiramide B which shows strong antibacterial activity against gram-positive bacteria such as Bacillus subtilis and weaker activities against gram-negative bacteria. However, the narrow structure-activity relationship of the pseudopeptide unit of moiramide B represents a formid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…130 Recent work has suggested that the sorbamide group in 25 and analogs with aromatic acyl tails can enhance enzyme binding, as well as demonstrating activity against Mycobacterium. 131 The outer membranes of G−ve bacteria contain an asymmetrical bilayer of LPS on the outside and phospholipids on the inside. The biosynthetic pathway for the lipid A portion of LPS is essential and conserved in most G−ve bacteria but is absent in humans, making it an attractive target for antimicrobial intervention 132,133 The lipid A biosynthesis pathway includes a range of targets, such as LpxC (uridine diphosphate-3-O-(hydroxymyristoyl)-N-acetylglucosamine deacetylase), 134 LpxA (UDP-N-acetylglucosamine acyltransferase), 135−137 LpxD (acyl-ACP-dependent N-acyltransferase), 135,138,139 and LpxH (UDP-2,3-diacylglucosamine pyrophosphate hydrolase).…”
Section: Previous Examples Of Clinical-stage Amps Include the Protegr...mentioning
confidence: 99%
See 1 more Smart Citation
“…130 Recent work has suggested that the sorbamide group in 25 and analogs with aromatic acyl tails can enhance enzyme binding, as well as demonstrating activity against Mycobacterium. 131 The outer membranes of G−ve bacteria contain an asymmetrical bilayer of LPS on the outside and phospholipids on the inside. The biosynthetic pathway for the lipid A portion of LPS is essential and conserved in most G−ve bacteria but is absent in humans, making it an attractive target for antimicrobial intervention 132,133 The lipid A biosynthesis pathway includes a range of targets, such as LpxC (uridine diphosphate-3-O-(hydroxymyristoyl)-N-acetylglucosamine deacetylase), 134 LpxA (UDP-N-acetylglucosamine acyltransferase), 135−137 LpxD (acyl-ACP-dependent N-acyltransferase), 135,138,139 and LpxH (UDP-2,3-diacylglucosamine pyrophosphate hydrolase).…”
Section: Previous Examples Of Clinical-stage Amps Include the Protegr...mentioning
confidence: 99%
“…Both 24 and 25 have broad spectrum low μM minimum inhibitory concentrations (MICs) against pathogens such as S. aureus , S. pneumoniae , E. coli , and P. aeruginosa . , In 2004, it was shown that 24 , 25 , and synthetic analogs inhibited the carboxyltransferase subunit (β-subunit) of the bacterial enzyme acetyl-CoA carboxylase (ACC) with nM affinity. In 2016, an X-ray crystal structure of moiramide B ( 25 ) bound S. aureus carboxyltransferase showed that the valine-methyl pyrrolidinedione subunit interacted with the enzyme oxyanion holes via an enol form, which mimics the enolate present in biotin . Recent work has suggested that the sorbamide group in 25 and analogs with aromatic acyl tails can enhance enzyme binding, as well as demonstrating activity against Mycobacterium …”
Section: Compounds With New Antibacterial Modes Of Actionmentioning
confidence: 99%